Assessing the diagnostic potential of SATB2 and β-catenin as biomarkers and therapeutic targets in pancreatic ductal adenocarcinoma - Noha Said Helal; Sara Maher; Safia Samir; Hesham A. Elmeligy; Mohammed A. Aboul-Ezz; Tarek Aboushousha; Mona Moussa (Journal of Cancer Research and Clinical Oncology)
Abstract Introduction Pancreatic ductal adenocarcinoma (PDAC) is associated with poor prognosis. The roles of the transcription factor special AT-rich binding protein-2 (SATB2) and β-catenin in PDAC have been a subject of controversy. We aimed to assess the diagnostic and prognostic impact of SATB2 and β-catenin in PDAC. Methods We analyzed 44 paraffin-embedded tissue blocks along with corresponding blood and pancreatic tissues. We evaluated SATB2 expression using immunohistochemistry (IHC) and enzyme-linked immunosorbent assay (ELISA). β-catenin was assessed using IHC and real-time polymerase chain reaction (qPCR). Results High SATB2 expression and low β-catenin expression were associated with a poor prognosis in PDAC, including advanced pathological tumor stage (pT-stage), pathological lymph node stage (pN-stage), and TNM stage. We found a positive correlation between SATB2 expression assessed by IHC and the concentration of SATB2 in both serum and tissue samples measured by ELISA. We observed a positive correlation between β-catenin expression assessed by IHC and β-catenin levels measured by qPCR. Conclusions SATB2 and β-catenin could provide valuable insights into the development of pancreatic cancer, and targeting them may be beneficial for the prevention and treatment of PDAC. The levels of SATB2 in serum show promise for the diagnosis and tumor invasion of pancreatic cancer.